Actual problems of definition of system of private law - Белуга, Юлія Миколаївна; Жилкова, Анастасія Андріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article theoretical and legal aspects of private law’s interpretation and its role in the legal system of Ukraine are studied by authors. Authors determine the correlation of private law with other branches of law